The effect of economic growth and poverty on stunting in Indonesia - Jumhur, Jumhur (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
Stunting is a critical issue affecting children under five years old, characterized by inadequate growth due to chronic malnutrition and recurrent infections, especially during the crucial first 1,000 days of life (from age 0 to 23 months). Stunting impacts not only height but also vital functions such as brain development and the immune system, potentially leading to decreased intelligence levels and increased susceptibility to diseases later in life. This study examines the impact of the growth of the Gross Regional Domestic Product (GRDP) in the primary, secondary, and tertiary sectors and the level of rural poverty on stunting in Indonesia. This research, which covers time series data from 2015-2020 across 32 provinces in Indonesia, employs a panel data regression model analysis method. The findings indicate that primary sector GRDP growth has a positive effect, whereas secondary sector GRDP negatively impacts stunting. However, the tertiary sector GRDP and rural poverty do not significantly affect stunting rates in Indonesia.